TUJUAN, FUNGSI, DAN HAKIKAT KURIKULUM DALAM IMPLEMENTASI PENDIDIKAN DI SEKOLAH DASAR - Muhammad Haekal Haekal; Fatimatul Baroroh (Institut Binamadani Indonesia, 2026)
The curriculum is the heart of the educational system, serving as the main guideline in the learning process at every level of education, particularly in elementary schools. This study aims to analyze the objectives, functions, and essence of the curriculum within the context of its implementation in elementary education, as well as the foundations underlying its development. The method employed is a literature review, examining various scientific journals, books, and educational policy documents. The results indicate that the elementary school curriculum has strategic functions, including adaptive, integrative, differentiative, preparatory, selective, and diagnostic functions. The essence of the elementary school curriculum is not merely a list of subjects, but a comprehensive design encompassing learning objectives, content, methods, and evaluation. The development of the elementary school curriculum must be based on philosophical, psychological, sociological, and juridical aspects in order to produce graduates who possess strong character, competence, and readiness to face future challenges. This study recommends the importance of a deep understanding of the nature of the curriculum among elementary school educators to ensure that the educational process is effective and meaningful for students.